Palynostratigraphical and oceanic anoxic events investigation in the Lower Jurassic Black Shale, Indus Basin, Pakistan - Ali , Fahad; Shiqi , Zhang; Ahmad , Rafique; Ali , Beenish; Iqbal , Hamid (Journal of Himalayan Earth Sciences, 2023)
The stratigraphy of Lower Jurassic in the Indus Basin, Pakistan, portrays the siliciclastic and carbonate strata in studied sections. The representative stratigraphic sections were sampled to investigate using carbon and oxygen isotopes (δ13C & δ18O), and palynology. Based on diagnostic palynomorphs from the Lower Jurassic, a single Hettigian-Pliensbachian assemblage biozone (HPABZ) is recognized. The oceanic anoxic event with a 2–3 ‰ negative shift in δ13C & δ18O across the Pliensbachian-Toarcian boundary is noted in the studied sections. The nature of the oceanic anoxic events are discussed and correlated with the established events worldwide.